Conversion of CH4 and CO2 to syngas and higher hydrocarbons using dielectric barrier discharge - Hwang, BB; Yeo, YK; Na, BK (KOREAN INSTITUTE CHEMICAL ENGINEERS, 2003)
The conversion of methane to syngas and other hydrocarbons in dielectric barrier discharge plasma under the presence of CO2 was investigated. Effects of the input voltage on the conversion of methane and CO, and the ratio of syngas were analyzed experimentally. The results of numerical simulations showed good quantitative agreement with those of experiments.